2009
DOI: 10.1007/s00210-009-0424-x
|View full text |Cite
|
Sign up to set email alerts
|

Safflor yellow B suppresses pheochromocytoma cell (PC12) injury induced by oxidative stress via antioxidant systemand Bcl-2 /Bax pathway

Abstract: Our previous study demonstrates that SYB produces a neuroprotective effect in vivo. In the present study, we investigated the protective effect of safflor yellow B (SYB) on the acute oxidative injury induced by H(2)O(2) and mechanisms in PC12 cells. H(2)O(2) was used to mimic in vitro model of the oxidative injury and to induce apoptosis in PC12 cells. The cells were pretreated with the different concentrations of SYB. The cell viability, lactate dehydrogenase (LDH) release, malondialdehyde (MDA), and superoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Our current study demonstrated that H 2 O 2 , as a prominent cause of apoptosis (Bissonnette et al 2004;Wang et al 2009), induced the typical apoptotic-like morphological changes in the human neuroblastoma SK-N-SH cells, such as the condensation of nuclear chromatin. When cells were pretreated with L-NBP, H 2 O 2 -induced apoptosis was significantly attenuated.…”
Section: Discussionsupporting
confidence: 50%
“…Our current study demonstrated that H 2 O 2 , as a prominent cause of apoptosis (Bissonnette et al 2004;Wang et al 2009), induced the typical apoptotic-like morphological changes in the human neuroblastoma SK-N-SH cells, such as the condensation of nuclear chromatin. When cells were pretreated with L-NBP, H 2 O 2 -induced apoptosis was significantly attenuated.…”
Section: Discussionsupporting
confidence: 50%
“…29 In a series of experimental studies, SY enhanced Bcl-2 expression and inhibited Bax and caspase-3 activation, thus attenuating neuronal apoptosis and spinal cord ischemia reperfusion injury 16 and protected PC12 cells from H 2 O 2 -induced injury and apoptosis. 30 SY also inhibited neuroinflammation which was mediated by Aβ 14 and oxygen-glucose deprivation in BV-2 cells. 18 The mechanisms of SY action include the phosphorylation of JAK2/STAT3 pathway, 14 the upregulation of Bcl-2/p22 (phox) expression 15 as well as the inhibition of oxidative stress/apoptosis and NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 88%
“…However, the present study was focused on investigating the pharmacological actions of safflower extraction and yellow pigment of safflower, monomer as hydroxysafflor yellow A and anhydrosafflor yellow B (Chen et al, 2000;Zang et al, 2002;Zhao et al, 2009b;Wang et al, 2009;Lin et al, 2011;Pan et al, 2012;Nie et al, 2012;. More studies ought to be explored on the pharmacological effects and possible mechanisms of other constituents isolated from safflower.…”
Section: Introductionmentioning
confidence: 99%